Preventing li-based cell fire from mechanical abuse - Siow, Jonathan Zhen Yang (Nanyang Technological University, 2024)
In a world driven by technology, the use of lithium batteries is on the rise. These batteries are widely used as they are lightweight and have high energy density. It is estimated that from 2022-2030, the lithium battery industry could grow over 30 percent annually. The prevalence of Active Mobility Devices (AMDs) demonstrates the high demand for batteries. However, each year, over 40 cases of reported fires in Singapore were caused by AMDs. These fires have resulted in the loss of lives and damage of property. Hence, while these batteries bring about many advantages, it still raises questions on the safety and reliability of their use. To better understand battery cell fires, more tests and studies have to be carried out. One such test is through mechanical abuse via the nail penetration test. From this test, the spread of fire across batteries can be further studied. A nail penetration system was designed and machined to carry out these experiments. The penetration system was designed to facilitate tests for 2 common types of batteries, namely Lithium Polymer (Li-Po) and Lithium Ion (Li-Ion). This would allow users to study different types of batteries with the same system. Tests were carried out on different cell size Li-Po batteries and Li-Ion batteries. Subsequently, the penetration test was coupled with overcharging of the batteries to observe any changes in the reaction. Lastly, the system was modified to allow cell fire extinguishers (CFEs) to be installed onto the system to determine the effectiveness of the CFEs in putting out battery fires. They were placed at different configurations to find the ideal position that would completely extinguish the fire. The data gathered has shown that the CFE can put out the cell fires.